Vitamin-D Deficiency: A Neglected Topic Alarms the Health Care Providers (Journal of Pakistan Orthopaedic Association, 2017)
ABSTRACTObjective: To assess the vitamin D3 in the study population and to compare it in the male female gender.Methods: This observational study was conducted from November 2016 to April 2017. Total 200 patients were selected through inclusion and exclusion criteria. Student’s t-test and SPSS version 20 to compare the mean levels of vitamin D3 in male and female genderResults: Male female ratio was found to be 1:1. Vitamin –D deficiency was found to be more prevalent in male gender as compared to females. Mean of the serum vitamin –D levels were 15.10+9.2ng/dl in men while it was 17.4+13.4 ng/dl in women. 139(69.5%) of the study population was found deficiency